Wages, Profits, and the Dynamics of Growth - Mossin, Jan (Quarterly Journal of Economics, 1966)
I. Introduction and summary, 376. — II. Fixed coefficients model: first analysis, 377.—III. Smooth substitution model: first analysis, 382.—IV. Fixed coefficients model: extended analysis, 385. — V. Smooth substitution I model: extended analysis, 394.—Appendix, 396.